Work Conflict Map: A Bibliometric Review of Key Elements and Their Development - Teratai, Nona Ratu Syifa Putri; Iskandar, Yusuf (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Work conflict is a pervasive phenomenon within organizational dynamics, garnering significant scholarly attention due to its multifaceted nature and profound impact on organizational performance and individual well-being. This bibliometric review scrutinizes the evolving landscape of work conflict literature, aiming to identify key trends, thematic clusters, and future research directions. By systematically analyzing a corpus of publications retrieved from reputable academic databases, including Scopus and Web of Science, this study provides a comprehensive overview of prevailing research themes and their development over time. Through methods such as overlay visualization, influential author analysis, clustering analysis, and density visualization, this study illuminates the intricate interplay between various constructs associated with work conflict, such as stress, job satisfaction, burnout, and leadership. Key findings underscore the evolving nature of work conflict research, highlighting emergent themes such as the impact of the pandemic, health-related concerns, and gender-specific experiences. Moreover, the study emphasizes the importance of proactive conflict management strategies and organizational support mechanisms in mitigating the negative consequences of work conflict. The findings of this study have significant implications for both researchers and practitioners, providing valuable insights into the current state of knowledge regarding work conflict and guiding future research endeavors aimed at fostering collaborative and innovative organizational cultures. Keywords: Work conflict, Bibliometric review, Research trends, Conflict management, Organizational dynamics.